3-Nitroadipate, a Metabolic Intermediate for Mineralization of 2,4-Dinitrophenol by a New Strain of a Rhodococcus Species - Blasco, Rafael (American Society for Microbiology, 1999)
The bacterial strain RB1 has been isolated by enrichment cultivation with 2,4-dinitrophenol as the sole nitrogen, carbon, and energy source and characterized, on the basis of 16S rRNA gene sequence comparison, as a Rhodococcus species closely related to Rhodococcus opacus. Rhodococcus sp. strain RB1 degrades 2,4-dinitrophenol, releasing the two nitro groups from the compound as nitrite. The release of nitro groups from 2,4-dinitrophenol occurs in two steps. First, the 2-nitro group is removed as nitrite, with the production of an aliphatic nitro compound identified by (1)H nuclear magnetic resonance and mass spectrometry as 3-nitroadipate. Then, this metabolic derivative is further metabolized, releasing its nitro group as nitrite. Full nitrite assimilation upon reduction to ammonia requires that an additional carbon source be supplied to the medium.